Active Mycobacterium Infection Due to Intramuscular BCG Administration Following Multi-Steps Medication Errors - MohammadReza Rafati; Bizhan Kouchaki (Research Center for Rational Use of Drugs (RCRUD), 2015)
Bacillus Calmette-Guérin (BCG) is indicated for treatment of primary or relapsing flat urothelial cell carcinoma in situ (CIS) of the urinary bladder. Disseminated infectious complications occasionally occur due to BCG as a vaccine and intravesical therapy.  Intramuscular (IM) or Intravenous (IV) administrations of BCG are rare medication errors which are more probable to produce systemic infections. This report presents 13 years old case that several steps medication errors occurred consequently from physician handwriting, pharmacy dispensing, nursing administration and patient family. The physician wrote βHCG instead of HCG in the prescription. βHCG was read as BCG by the pharmacy staff and 6 vials of intravesical BCG were administered IM twice a week for 3 consecutive weeks. The patient experienced fever and chills after each injection, but he was admitted 2 months after first IM administration of BCG with fever and pancytopenia. Unfortunately four month after using drug, during second admission duo to cellulitis at the sites of BCG injection the physicians diagnosed the medication error. Using handwritten prescription and inappropriate abbreviations, spending inadequate time for taking a brief medical history in pharmacy, lack of verifying name, dose and wrote before medication administration and lack of considering medication error as an important differential diagnosis had roles to occur this multi-steps medication error.